The knight at dawn - Osborne, Mary Pope (Osborne, Mary Pope. Magic tree house series ;, 1993)
Eight-year-old Jack and his younger sister Annie use the magic treehouse to travel back to the Middle Ages, where they explore a castle and are helped by a mysterious knight.